Altered stress and fear responses in the VPA rat model of autism: Behavioral dissociation across tactile, nociceptive, and social contexts - Debora Hashiguchi; Ana Luiza Dias; Rodrigo Neves Romcy-Pereira (PLoS ONE, 2026)
Altered sensitivity to environmental stimuli is a core feature of autism spectrum disorder (ASD) that may drive vulnerability to stress-related and anxiety disorders. To investigate this relationship, we evaluated autonomic and behavioral responses to tactile, nociceptive, and social stressors in juvenile Wistar rats prenatally exposed to valproic acid (VPA), a well-established model of ASD. VPA-exposed and saline-treated control (CTL) rats were subjected to a behavioral paradigm measuring defecation, freezing, and ultrasonic vocalizations (USVs) in response to handling, electro-tactile stimulation, classical fear conditioning, and an emotional contagion task. Compared to CTLs, VPA rats exhibited sustained hyperdefecation during handling and a higher prevalence of defecation during electro-tactile stimulation, independent of freezing changes. During fear conditioning, VPA rats demonstrated a delayed onset but subsequent enhancement of freezing responses, alongside disrupted temporal coordination between freezing and defecation behaviors. 22-kHz USVs positively correlated with freezing across both groups. In the emotional contagion task, observing a distressed conspecific increased freezing prevalence and suppressed vocalization rates in both cohorts; however, these effects were prolonged in VPA rats, which showed persistent freezing and an earlier reduction in vocalization rate. These findings indicate that VPA-treated rats display heightened stress reactivity, habituation deficit and suggest disrupted coordination of fear responses, supporting the VPA model as a relevant tool for investigating the neurobiological basis of stress vulnerability and social dysfunction in ASD.